Development of a Dosage form for a Photoswitchable Local Anesthetic Ethercaine - Alexey Noev; Natalia Morozova; Nikita Suvorov; Yuriy Vasil'ev; Andrei Pankratov; Mikhail Grin (MDPI AG, 2023)
The toxicity of local anesthetics is a serious problem, given their widespread use. One of the main causes of the side effects of local anesthetics is their non-selectivity of action in the body. A possible way to increase the selectivity of the action of drugs is to use the photopharmacology approach. Previously, we described the light-controlled local anesthetic ethercaine, the biological effect of which can be controlled using light, thereby increasing its selectivity of action. An important limitation of ethercaine was its low solubility in water, limiting the potential of this compound. In this work, we developed a dosage form of ethercaine, which allowed us to increase its solubility from 0.6% to 2% or more. The resulting 1% solution of ethercaine hydrochloride in 4% Kolliphor ELP had high biological activity on the surface anesthesia model, while demonstrating low acute toxicity in mice with intravenous administration (4-5 times less than that of lidocaine).